(untitled) (International Current Pharmaceutical Journal, 2015)
Aim of the present study was to evaluate the effect of flurbiprofen, which is a member of non-steroidal anti-inflammatory drug group (NSAIDs), on postoperative pain treatment. From September 2013 to May 2014, total of 250 patients were surveyed to perform a systematic evaluation of postoperative pain by comparing flurbiprofen with two other kinds of NSAIDs (diclofenac and ketorolac) and isotonic saline in a double-blind, randomized, placebo-controlled study. Patients were randomized for treatment: 65 cases received flurbiprofen, 60 cases received diclofenac sodium, 60 cases received ketorolac and 65 cases received the placebo (0.9% isotonic saline) (control group). After 24-hours of surgery patients treated with flurbiprofen, ketorolac, and diclofenac showed the lowermost PPI scores compared with those treated with 0.9% isotonic saline (P<0.05). Moreover, flurbiprofen-treated patients also had the lowest PRI(R)T scores (P<0.05). When the pain rating index was examined by subclass, a significantly lower PRI(R)S score was detected in the flurbiprofen group at 24 hours (P<0.05). However, at the 96-hour time point, no differences that were found in PPI and PRI[R] scores between the ketorolac, diclofenac, and flurbiprofen groups, whereas the control group was significantly less effective than the NSAID drugs. Flurbiprofen seemed to be the most effective NSAID for the treatment of pain after internal fixation of fracture, even though at 24 hours after surgery pain was at a maximum. DOI: http://dx.doi.org/10.3329/icpj.v4i3.21935 International Current Pharmaceutical Journal, February 2015, 4(3): 367-369